Design and Characteristic Investigation of Novel Dual-Stator V-Shaped Magnetic Pole Six-Phase Permanent Magnet Synchronous Generator for Wind Power Application. Issue 14 (28th November 2020) - Kumar, Raja Ram; Chetri, Chandan; Devi, Priyanka; Saket, Ram Khelawan; Blaabjerg, Frede; Sanjeevikumar, Padmanaban; Holm-Nielsen, Jens Bo
Abstract: This paper describes the characteristic investigation of the Novel Dual-stator V-Shape Magnetic Pole Six-Phase Permanent Magnet Synchronous Generator (NDSVSMPSP-PMSG) for wind power application. The proposed generator has V-shaped embedded magnetic pole in the rotor and six-phase winding in both the stator. The proposed generator has high-power density and high efficiency. For emphasizing the significance of the proposed generator, the characteristics of the NDSVSMPSP generator are analyzed and compared to one of the traditional generators, i.e ., the Dual-stator Surface Mounted Six-Phase Permanent Magnet Synchronous Generator (DSSMSP-PMSG). For the design and characteristic investigation of both the generator, Finite Element Method (FEM) is chosen because of its high accuracy. Two modes of FEM analysis are considered, namely magneto-statics and transients. The magneto static analysis is used for the study of flux line and flux density distribution, while the transient analysis is considered for the generator's characteristic investigation. The performance characteristics such as generated Electromotive Force (EMF) for both inner and outer stator, Percentage Total Harmonic Distortion (THD) of developed voltage, Developed EMF vs rpm, terminal voltage vs. current, developed rotor torque vs time, percent (%) ripple content in torque, and percent efficiency vs current for both generators are investigated. As a result, it can be stated that the power density and reliability of the proposed generator is higher than that of the traditional generator.